1991
DOI: 10.3168/jds.s0022-0302(91)78399-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism of Lactating Ewes Fed Rumen-Protected Methionine and Lysine

Abstract: Twenty multiparous, crossbred, black-faced ewes and their newborn twin lambs were assigned to one of four dietary treatments in a 2 x 2 factorial experiment to examine the effects of increased supply of CP or a mixture of encapsulated methionine and lysine or both on the performance of ewes and their nursing twin lambs. Ewes were fed ad libitum amounts of either a 10.2% low CP diet or a 16.2% moderate CP diet with or without additional encapsulated amino acids. Nitrogen metabolism trials were conducted simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
10

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 24 publications
5
19
1
10
Order By: Relevance
“…L-lactate and 尾-hydroxybutyrate were significantly increased in relation to the initial level by the groups receiving additional methionine but not with leucine or without amino acid supplementation. This contradicts results of Lynch et al [23] in lactating ewes who found no effects of methionine supplementation on lactate. Similar to the present study, they also did not observe an influence of an increased methionine supply on insulin, glucose, triglycerides and non-esterified fatty acids.…”
Section: Effects Of Leucine and Methionine On Metabolic Indicatorscontrasting
confidence: 93%
See 1 more Smart Citation
“…L-lactate and 尾-hydroxybutyrate were significantly increased in relation to the initial level by the groups receiving additional methionine but not with leucine or without amino acid supplementation. This contradicts results of Lynch et al [23] in lactating ewes who found no effects of methionine supplementation on lactate. Similar to the present study, they also did not observe an influence of an increased methionine supply on insulin, glucose, triglycerides and non-esterified fatty acids.…”
Section: Effects Of Leucine and Methionine On Metabolic Indicatorscontrasting
confidence: 93%
“…In the state of a distinct deficiency the selective supplementation of the respective limiting amino acid should have increased nitrogen utilisation by a higher incorporation into milk protein and a correspondingly lower excretion provided N intake remained approximately constant. Lynch et al [23] found in lactating ewes a clearly increased efficiency of nitrogen utilisation with low intake of nitrogen (crude protein) and a simultaneous supply of protected methionine. However, these results were more likely a result of the decreased content of diet protein than of the simultaneously supplemented methionine.…”
Section: Effects Of Leucine and Methionine On Metabolic Indicatorsmentioning
confidence: 99%
“…The low efficiency is likely because sheep have higher requirements than cattle for sulfur-containing amino acids, due to their wool production (Bocquier et al, 1987). Lynch et al (1991) demonstrated that the supplementation of rumen-protected methionine and lysine to lactating sheep caused a significant increase in the growth rate of the suckling lambs. At similar physiological stages, sheep tend to have higher passage rates than cattle (Van Soest, 1994) and subsequently greater escape of feed protein.…”
Section: Model Developmentmentioning
confidence: 99%
“…The profile of AA reaching ruminants' small intestine is an important determinant of milk and wool production as well as productivity of growing ruminants (Lynch et al, 1991;Urbaniak, 1995b;Rulquin et al, 1998). However, many research papers reported that AA profile of protein absorbable from the small intestine may not always be optimal for maximal performance of different kinds of ruminant production -milk, growth and wool (Schwab 1994;Metcalf et al, 1996;Rulquin et al, 1998).…”
Section: Introductionmentioning
confidence: 99%